SYSTEMATIC REVIEW OF ORAL JANUS KINASE INHIBITORS IN ALOPECIA AREATA: INSIGHTS FROM 2020 TO 2025 STUDIES - Anna Mandecka; Kornela Kotucha-Cyl; Weronika Komala; Natalia Guzik; Joanna Gerlach; Dorota Plechawska; Joanna Kaźmierczak; Karolina Witek; Marta Nowocień (International Journal of Innovative Technologies in Social Science, 2025)
Background: Alopecia areata (AA) is an autoimmune, non-scarring hair loss disorder with variable clinical presentations. Its pathogenesis involves immune privilege collapse of the hair follicle, CD8+ T-cell activation, and cytokine signaling—particularly IFN-γ and IL-15—via the JAK/STAT pathway. Recent studies highlight Janus kinase (JAK) inhibitors as promising therapeutic agents for moderate-to-severe AA.Objectives: This systematic review aimed to evaluate the efficacy and safety of oral JAK inhibitors in the treatment of adolescent and adult patients with AA based on studies published between 2020 and 2025.Material and Methods: Following PRISMA 2020 guidelines, a comprehensive search of PubMed, Cochrane Library, and ClinicalTrials.gov was conducted for studies assessing oral JAK inhibitors (e.g., baricitinib, ritlecitinib, deuruxolitinib) in AA. Inclusion criteria encompassed RCTs, observational studies, and interventional trials involving patients ≥12 years old with moderate-to-severe AA.Results: Ten studies met the criteria, including seven RCTs. Efficacy was measured predominantly by the Severity of Alopecia Tool (SALT) score. Baricitinib and deuruxolitinib consistently demonstrated superior outcomes compared to placebo and traditional therapies, with up to 41.5% of patients achieving SALT ≤20 at 24 weeks. Long-term data confirmed sustained benefits. Adverse events were mostly mild (e.g., URTI, headache, acne); serious events and discontinuations were rare.Conclusions: Oral JAK inhibitors represent an effective and generally well-tolerated option for treating moderate-to-severe AA. Their targeted mechanism offers advantages over traditional immunosuppressants, and accumulating long-term data support their integration into therapeutic guidelines.